Penerapan Metode Promethee Dalam Sistem Pendukung Keputusan Penetapan Penerima Kartu Indonesia Sehat (KIS) - Siregar, Reva Octaviani; Irmayani, Deci; Masrizal, Masrizal (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Health is a state of well-being of body, soul and society that enables everyone to live productively socially and economically. Therefore, health is the most important element in human life. Health is closely related to economic conditions. factors that affect human health such as healthy food and drinks, a healthy environment and healthy living habits will be fulfilled. Conversely, if a bad economy will make it difficult for individual people to meet some of these factors, if these conditions are ignored, the individual community will find it difficult to improve their health. The problem that occurred at Galang Health Center was the unsatisfactory selection of KIS (Kartu Indonesia Sehat) participants. the selection of KIS (Kartu Indonesia Sehat) participants requires a decision support system (DSS) to speed up and make it easier to make decisions. Decision support systems are used to assist decision making in an organization to facilitate decision making. Where no one knows exactly how decisions should be made. The Promethee method (Preference Ranking Organizational Method for Enrichment Evaluation) is a method used to determine priority (order) in multi-criteria analysis. With the Promethee method, the problem of choosing KIS (Kartu Indonesia Sehat) participants is feasible to use in this study, the stages of research carried out in this study are starting from data collection, problem analysis, method analysis, design and testing of applications to be built, the purpose of this research is to solve the problems of the participants. KIS (Kartu Indonesia Sehat), which have been unsatisfied in terms of the decision of KIS (Kartu Indonesia Sehat) recipients. The results showed that of the three KIS (Kartu Indonesia Sehat) participants who were tested, there were two participants who deserved KIS (Kartu Indonesia Sehat) based on the results of the assessment of the five criteria used so that the calculation results using the Promethee method showed that the net flow from each of the alternatef is -1 for alternative 1 and 0.2 for alternative 2 and 0.8 for the third alternative.